2019
DOI: 10.1111/cfs.12655
|View full text |Cite
|
Sign up to set email alerts
|

Perceived social support, perception of competence, and hope among Chinese children with attention deficit hyperactivity disorder in a Chinese context: Children's perspective

Abstract: This paper reports on the results of a study (n = 113 children with attention deficit hyperactivity disorder) that examined the effects of the children's perception of the social support (PSS) they receive from their mothers, fathers, teachers, and friends on their sense of competence and hope. PSS explained 13% of the children's overall sense of competence and 4% of their sense of hope. In the perspective of children with attention deficit hyperactivity disorder, the amount of maternal support, both in terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…The results of the study shed light on the need for a shift away from an individual-focused approach to a contextually based approach in enhancing social functioning of children with ADHD (Mikami & Normand, 2015) when service programs are aimed not only at modifying the behavior of child with ADHD but also include service support for their teachers and parents. This study has expanded our knowledge of the protective processes of the peer functioning of children with ADHD, which in turn supports strengths-based social work practice supposing the identification of protective factors as well as risk factors (Ma et al, 2020).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The results of the study shed light on the need for a shift away from an individual-focused approach to a contextually based approach in enhancing social functioning of children with ADHD (Mikami & Normand, 2015) when service programs are aimed not only at modifying the behavior of child with ADHD but also include service support for their teachers and parents. This study has expanded our knowledge of the protective processes of the peer functioning of children with ADHD, which in turn supports strengths-based social work practice supposing the identification of protective factors as well as risk factors (Ma et al, 2020).…”
Section: Discussionsupporting
confidence: 66%
“…Knowledge of the predictive power of risk factors at different levels (individual, family, and social) in one model may help improve the effectiveness of the prevention of and intervention in the peer rejection of children with ADHD. A study of protective mechanisms may enhance our understanding of the peer rejection of children with ADHD (Fraser et al, 1999) and improve the efficiency of social work with these children and their families (Ma et al, 2020). A simultaneous study of the protective factors at each of the three levels could reveal which factors of which level may be more protective than others.…”
Section: Introductionmentioning
confidence: 99%
“…Three studies found that children and youth with ADHD reported perceiving less social support from friends in comparison to a normative sample and their peers [ 58 , 69 ], with Rokeach and Wiener reporting significantly lower self-reported friendship quality for 16–18 year olds [ 74 ]. In a study without a comparison group, children with ADHD reported that PSS was the least available from their friends [ 68 ]. On the whole, the studies reviewed indicate children with ADHD report or are observed to have more conflict with their friends, fewer positive features of friendship quality, and lower levels of social support [ 26 , 28 31 , 47 , 48 , 52 , 53 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Participants with ADHD were mostly male, 68.4% and 63.7% of TD participants were male. The IQ of participants varied between 70-120 on the Wechsler Abbreviated Scale of Intelligence [95,96], though five studies did not report IQ eligibility criteria [59,66,68,73]. In five studies, participants' diagnosis was confirmed using the DSM-5, seven studies used the DSM-IV, two studies used the DSM-IV-TR, DISC-IV or the KSADS [85], and one study used the ICD-10 F90 Hyperkinetic disorder criteria [51] or DSM-III-R [51].…”
Section: Participantsmentioning
confidence: 99%
“…The father-child relationship is shown to have significant effects on older children's cognitive and physical competence whilst the mother-child relationship is significantly correlated with younger children's general self-worth . Notably, children with ADHD perceived paternal support as lowest when compared to that received from mothers, teachers, and friends (Ma, Lai, & Xia, 2020).…”
Section: Impacts Of Adhd On Children and Familiesmentioning
confidence: 93%